Properties of glycerol and ethylene glycol mixture based SiO2-CuO/C hybrid nanofluid for enhanced solar energy transport - Akilu, S. (Elsevier B.V., 2018)
Hybrid nanofluids are a novel class of colloidal fluids which have drawn significant attention due to potential tailoring of their thermo-physical properties for heat transfer enhancement by a combination of more than one nano-additive to meet specific requirements of an application. In the present work, ceramic copper oxide/carbon (SiO2-CuO/C) nanoparticles in 80:20 (wt) composition were prepared by ultrasonic-assisted wet mixing technique. The hybrid nanofluid was formulated by dispersing the nanoparticles into a base fluid mixture of 60:40 ( by mass) glycerol and ethylene glycol (G/EG) using the two-steps method. The influence of nanoparticles on the augmentation of specific heat, thermal conductivity and viscosity was examined in the volume concentration range of 0.5â2.0 in the temperature range of 303.15â353.15 K. The results demonstrate that the synthesized SiO2-CuO/C hybrid nanoparticles enhanced the thermo-physical properties of the base fluid mixture which is higher than using SiO2 alone. In the case of SiO2âG/EG nanofluid, the specific heat capacity decremented by a maximum value of 5.7 whereas the thermal conductivity and viscosity incremented by 6.9 and 1.33-times as compared with G/EG at maximum volume concentration of 2.0 at a temperature of 353.15 K. Comparatively, a reinforcement of 80 SiO2 with 20 CuO/C in G/EG mixture led to thermal conductivity and viscosity enhancement by 26.9 and 1.15-times, respectively with a significant reduction of specific heat by 21.1. New empirical correlations were proposed based on the experimental data for evaluation of thermophysical properties. Â© 2017 Elsevier B.V.